Judgment’s motivation of Criminal Court in the light of the law 17/07 amending and supplementing the law of criminal procedure. - Chemseddine, Saber; Zaoueche, Rabiaa (Journal of Human Sciences, 2021)
Modern penal legislation seeks to surround the decisions of penal courts with all the adequate guarantees to bring judgments closer to the fact and to the law, and taking into account the gravity of the acts it examines on one hand, and the severity of the sanctions it imposes on the other, the decision of motivating the judgments of the criminal courts is one of the most important changes made to the working system of these courts. The Algerian legislator requested, in accordance with Law 17/07, the need to motivate the judgments rendered by penal court, embodying the right of the litigant to a fair trial and to the consecration of judicial security as a guarantee for the judge, and to control the judgments handed down by him on the other hand.